Why Civil Resistance Fails: The Saffron Uprising in Myanmar, 2007 (In Factis Pax: Journal of Peace Education and Social Justice, 2019)
This article examines why the 2007 Saffron Uprising in Myanmar failed to achieve its strategic objectives. By applying Ackerman and Kruegler’s (1994) principles of nonviolent conflict, the author examines how the strategic and tactical choices employed by campaign leaders minimized the campaign’s ability to achieve its goals. The findings suggest that the major reason the movement failed is associated with two factors: first, movement leaders were unable to create defection in security forces and in the civilian bureaucracy; second, the organizers were unable to build organizational strength and to produce contingency leadership. The other reasons for the failure include the movement leaders’ inability to generate wide external support and that they did not assess the events and options in light of strategic decision making. These findings are essential not only for understanding the campaign’s failure, but to building theory. They alert scholars and activists to acknowledge the type of foreign support required for modern campaigns to succeed. The case also underscores the significance of education and preparation through training so that activists understand the dynamics of nonviolent conflict and are able to respond strategically to trying circumstances.
Keywords: nonviolence; Saffron Uprising; campaign; loyalty shifts; monks